Students' Time Style Analysis of Achievements; Analisis Gaya Waktu Siswa Berprestasi - Faiz Ahmad Hunafa; Henry Aditia Rigianti (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2022)
This research started from problems in the learning of underachieving students who tend to be lazy to learn and lazy when learning. This encourages research with the aim of improving critical thinking skills. Furthermore, a research design for an inquiry-based learning strategy was developed with a 5E learning cycle to improve critical thinking skills. The research method used is a quasi-experimental research design with a pretest - posttest control group design. The results of the hypothesis test analysis obtained that the experimental group's critical thinking ability was better than the control group after learning. Thus, inquiry-based learning with the 5E learning cycle is very significant in improving critical thinking skills compared to conventional learning.